The first detection of Rickettsia aeschlimannii and Rickettsia massiliae in Rhipicephalus turanicus ticks, in northwest China. Issue 1 (December 2015) - Wei, Qing-Qing; Guo, Li-Ping; Wang, An-Dong; Mu, Lu-Meng; Zhang, Ke; Chen, Chuang-Fu; Zhang, Wan-Jiang; Wang, Yuan-Zhi
Abstract Background Rickettsia spp. belonging to the spotted fever group (SFG) cause infections in humans, domestic animals and wildlife. At least five SFG rickettsial species have been reported in China, but the occurrence ofRickettsia aeschlimannii andR. massiliae in ticks has not been characterized to date. Findings A total of 114 adult ticks were collected from sheep in Yining County, Xinjiang Uygur Autonomous Region, in northwest China. The ticks were identified from morphological and molecular characteristics. All samples were examined by polymerase chain reaction (PCR), and six genetic markers were used to determine theRickettsia spp. in the ticks. The ticks collected were identified asRhipicephalus turanicus . Three different lineages ofRh. turanicus from Yining County were discovered on phylogenetic analysis of16S rDNA andcox1 . Twenty-one of the 114 samples (18.42%) were positive for rickettsial agents. Phylogenetic analysis based on six genetic sequences showed that three rickettsial species were present, namely:R. aeschlimannii (19.05%, 4/21), R. massiliae (19.05%, 4/21) andR. sibirica variant (61.90%, 13/21), which is clustered in the clade ofR. sibirica subsp.sibirica . Conclusions This is the first description ofR. aeschlimannii andR. massiliae in China.R. massiliae, R. aeschlimannii andR. sibirica variant co-circulate in the region of the China-Kazakhstan border, in northwest China. Rickettsial agents in ticks of the genusRhipicephalus from migrant birds, transported livestock, wildlife and human beings should be investigated further in the region of the China–Central Asian border.